IT Enabled Services - Uesugi, Shiro; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
As the global economy turns more and more service oriented, Information Technology-Enabled Services (ITeS) require greater understanding.  Increasing numbers and varieties of services are provided through IT.  Furthermore, IT enables the creation of new services in diverse fields previously untouched. Because of the catalyzing nature of internet technology, ITeS today has become more than “Outsourcing” of services.  This book illustrates the enabling nature of ITeS with its entailment of IT, thus contributing to the betterment of humanity.  The scope of this book is not only for academia but also for business persons, government practitioners and readers from daily lives.  Authors from a variety of nations and regions with various backgrounds provide insightful theories, research, findings and practices in various fields such as commerce, finance, medical services, government and education.  This book opens up a new horizon with the application of Internet-based practices in business, government and in daily lives.  Information Technology-Enabled Services works as a navigator for those who sail to the new horizon of service oriented economies.
IT-Enabled Services -- The Effects Of Similarities To Previous Buyers On Trust And Intention To Buy From E-Commerce Stores: An Experimental Study Based On The Svs Model -- Information Diffusion And Dissipative Effect On Social Networks -- Construction Of An Appropriately Professional Working Environment For It Professionals: A Key Element Of Quality It-Enabled Services -- A Community Based Trust Establishing Mechanism For A Social Web Service -- Smartphones: The Next Generation Medication Administration Tool -- Weaknesses Of The E-Government Development Index -- Computer Mediated Communication And Telecollaboration For Language Learning: Issues Of Technology -- Transforming The Personal Response System To A Cloud Voting Service -- Case Studies Of User Interface Design On Internet Banking Websites And Mobile Payment Applications In Thailand.-   Japanese Students’ Behavior Toward E-Commerce -- Exchange Of Information And Values Taking Privacy Into Consideration -- Real Name Social Networking Services And Risks Of Digital Identity. Can We Manage Our Digital Identity? -- Information-Offering By Anonymous Users In A Japanese Human Flesh Search Analysis Of Motivation In A Social Media Platform.
Keywords: Application software; Physics; E-commerce.; Information Systems Applications (incl. Internet).; Applications of Graph Theory and Complex Networks; e-Commerce/e-business.